A randomized prospective pilot trial of Web‐delivered epilepsy stigma reduction communications in young adults. (27th September 2017) - Sajatovic, Martha; Herrmann, Lynn K.; Van Doren, Jamie R.; Tatsuoka, Curtis; Welter, Elisabeth; Perzynski, Adam T.; Bukach, Ashley; Needham, Kelley; Liu, Hongyan; Berg, Anne T.
Summary: Objective: Epilepsy is a common neurological condition that is often associated with stigmatizing attitudes and negative stereotypes among the general public. This randomized controlled trial (RCT) tested two new communication approaches targeting epilepsy stigma versus an education‐alone approach. Methods: Two brief stigma‐reduction videos were developed, informed by community stakeholder input; one highlighted role competency in people with epilepsy; the other highlighted social inclusion of people with epilepsy. A control video was also developed. A Web‐based survey using a prospective RCT design compared effects of experimental videos and control on acceptability, perceived impact, epilepsy knowledge, and epilepsy stigma. Epilepsy knowledge and stigma were measured with the Epilepsy Knowledge Questionnaire (EKQ) and Attitudes and Beliefs about Living with Epilepsy (ABLE), respectively. Results: A total of 295 participants completed the study. Mean age was 23.1 (standard deviation = 3.27) years; 59.0% were male, and 71.4% were white. Overall, respondents felt videos impacted their epilepsy attitudes. EKQ scores were similar across videos, with a trend for higher knowledge in experimental videos versus control (p = 0.06). The role competency and control videos were associated with slightly better perceived impact on attitudes. There were no differences between videos on ABLE scores (p = 0.568). There were subgroup differences suggesting that men, younger individuals, whites, and those with personal epilepsy experience had more stigmatizing attitudes. Significance: This RCT tested communication strategies to improve knowledge and attitudes about epilepsy. Although this initial effort will require follow‐up, we have demonstrated the acceptability, feasibility, and potential of novel communication strategies to target epilepsy stigma, and a Web‐based approach for assessing them.